Factors Affecting the Competitiveness Enhancement of Preserved Seafood Industry in Thailand: Literature Review - Ninubon, Suradeach; Lalitsasivimol, Woraluck; Jankingthong, Korkaew; Thongpoon, Siriluck (Economics and Business Administration Journal Thaksin University, 2022)
At present, it has high demand of preserved seafood from world population. The Food and Agriculture Organization of the United Nation (FAO) estimated for the grow up 35% of the world preserved seafood consumption in 2050 for 9.6 billion peoples and estimated the world’s demand for seafood is approximately 21.8 kilograms per person, up from 20.3 kilograms per person in 2015. Causing the preserve seafood is Important for economic growth continuously. This is because humans need food. There are many food sources. And most importantly, food sources that come from the sea which has been popular from the past. This study aim to literature review to related the development of the research framework for creating the competitiveness enhancement of preserved seafood industry in Thailand. The result of the literature review found that increasing competitiveness capability of preserved seafood industry in Thailand will be able to give an industry competitive advantage. Therefore, preserved seafood industry operators in Thailand and the importance of the application should be emphasized to develop and increase the competitiveness of the industry, through human capital and adaptability and entrepreneurial orientation for the future sustainability.